Institutionalization of Performance Accountability System for Government Institutions in Malang City Government - Fransiska Iing Mariandini; Gugus Irianto; Nurkholis Nurkholis (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2018)
Abstract: Institutionalization of Performance Accountability System for Government Institutions in Malang City Government. This study aimed to understand the institutionalization of Malang City Government’s SAKIP with accordance to Presidential Regulation No. 29/2014. This study found high commitment to support national development plan, and it affected planning, budgeting, and Regional Organizations (OPD) internal evaluation positively. This study also found indications of isomorphism and decoupling. The evidences of isomorphism were as follows; the existence of formal insistence of strict laws and informal insistence of the East Java Provincial Government as the indication of coercive; the adoption of Civil Servant’s Performance Agreement formulation as mimetic view; joint effort for internal capacity building among KEMENPAN-RB, East Java Provincial Government, and PT. Jakarta Traspac as a normative proof. Meanwhile, indications of decoupling were as follows; the OPD’s mindset was not an outcome-oriented mindset, low awareness of the importance of creating performance data management Standard Operating Procedure (SOP), and low utilization of performance information. Keywords: SAKIP, Isomorphism, decouplingAbstrak: Institusionalisasi Sistem Akuntabilitas Kinerja Instansi Pemerintah di Pemerintah Kota Malang. Penelitian ini bertujuan untuk memahami institusionalisasi SAKIP di Pemerintah Kota Malang sesuai dengan Perpres No. 29 tahun 2014. Penelitian ini menggunakan paradigma post positive. Analisis dan interpretasi data dilakukan berdasarkan teori New Institutional Sociology (NIS). Hasil penelitian menunjukkan tingginya komitmen untuk mendukung rencana pembangunan nasional yang berdampak pada pembenahan perencanaan, penganggaran, dan evaluasi internal Organisasi Perangkat Daerah (OPD). Hasil analisis menemukan indikasi isomorphism dan decoupling. Terjadinya isomorphism dibuktikan dengan: desakan formal dari aturan hukum dan desakan informal dari Pemerintah Provinsi (Pemprov) Jatim merupakan gejala coercive; pengadopsian penyusunan perjanjian kinerja Aparatur Sipil Negara sebagai gambaran mimetic; dan kerjasama antara KEMENPAN-RB, Pemprov Jatim, dan PT. Jakarta Traspac untuk peningkatan kemampuan internal organisasi merupakan bukti normative. Indikasi decoupling ditunjukkan oleh mindset OPD yang belum berorientasi outcome, rendahnya kesadaran penyusunan Standard Operating Procedure (SOP) pengelolaan data kinerja, dan rendahnya pemanfaatan informasi kinerja. Kata kunci: SAKIP, Isomorphism, decoupling